The Differences in the Implementation of Make a Match and the Round Table Learning Methods on Economics Learning Outcomes - Prayitno, Putra Hilmi (Unversitas Negeri Malang, 2017)
Abstract Economics learning outcomes in X Social Science Class in State Senior High School 2 of Lamongan is Relatively Low, Researcher know this condition was based on the last test scores from economic teacher. To solve this problem, teachers are expected to the make the learning ambience more interesting. If the teacher can create an attractive learning ambience, the student’s learning outcomes will increase. One of strategy that can be applied by teachers is using cooperative learning. Cooperative learning strategies consist of several kinds. In this research, Researcher applied two kind of cooperative learning methods; make a match and round table. The purpose of this research is to determine the difference in student’s economics learning outcomes who taught by make a match and round table. This research used quasi-experimental research (quasi-experiment) with nonequivalent control group with pretest-posttest design. The results of this research concluded that there are differences in economics learning outcomes who taught by make a match and a round table in the X Social Science Class in State Senior High School 2 of Lamongan. The learning results who taught by make a match methods was upper than students who are taught by a round table methods. Keywords: Make a Match, Round Table, Learning Outcomes DOI: 10.17977/um013v1i12017p021